Graphological and Lexicogrammatical Analysis of Narrative Text Written By 6th Semester Students of English Department at HKBP Nommensen University - Manurung, Anjeli Artha Br; Manurung, Lastri Wahyuni; Sidabutar, Usman (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
Narrative writing allows students to demonstrate their ability to tell stories, apply grammatical knowledge, and use vocabulary creatively. This study aims to find out the graphological and lexicogrammatic constituency in narrative texts by 6th-semester students of HKBP Nommensen University. This study uses Halliday & Matthiesen's theory. This study uses a qualitative descriptive method; the instruments used in this research are observation and document analysis. The research data are in the form of narrative texts written by sixth-semester students. The study results found that most of the narrative text writing by 6th-semester students had a graphological and lexicogrammatical constituency. In the graphological constituency, some sentences total 58, and the sub-sentences have a total number of 122. In the lexicogrammatical constituency, there are complex clauses with a total number of 58, and the clauses have a total of 122. This means that from the findings of this study on graphological and lexicogrammatical analysis, the researcher found that students have sufficient/proficient writing skills because they use varied sentences, thus developing their ability to create sentence variations and cohesion in writing narrative texts.